ANALISA REMBESAN 2 DIMENSI MENGGUNAKAN METODE ELEMEN -HINGGA DENGAN PROGRAM BANTU KOMPUTER - Ahyadi , Hendra
Abstract : Water flow that pass holed material could make effective volt changes that gives pressure to the ground if this pressure could not be controled, will make alt of damaged, for example structure damaged and unstable for helping solve that problem, need a model, that is mathematic one, that could used as a tool to predict real condition from thase water flow to the ground. This thesis is trying to make two dimension water flow mathematic model, for stable flow or unstable flow condition, to prove that finite element method is good enough to solve water flow to the ground problems. This mathematic model then implemented into computer program using fortran language. To case operate this program, a program as made that using Visual Basic language, so that this program could be run in its window. To test the accurancy of model from this numerik model compare with from SEEP/W program to simple cases, for example Darn Homogen and Darn Heterogen cases.